MR‐CT registration using a Ni‐Ti prostate stent in image‐guided radiotherapy of prostate cancer. Issue 6 (24th May 2013) - Korsager, Anne Sofie; Carl, Jesper; Østergaard, Lasse Riis
Abstract : Purpose: In image‐guided radiotherapy of prostate cancer defining the clinical target volume often relies on magnetic resonance (MR). The task of transferring the clinical target volume from MR to standard planning computed tomography (CT) is not trivial due to prostate mobility. In this paper, an automatic local registration approach is proposed based on a newly developed removable Ni‐Ti prostate stent. Methods: The registration uses the voxel similarity measure mutual information in a two‐step approach where the pelvic bones are used to establish an initial registration for the local registration. Results: In a phantom study, the accuracy was measured to 0.97 mm and visual inspection showed accurate registration of all 30 data sets. The consistency of the registration was examined where translation and rotation displacements yield a rotation error of 0.41° ± 0.45° and a translation error of 1.67 ± 2.24 mm. Conclusions: This study demonstrated the feasibility for an automatic local MR‐CT registration using the prostate stent.